2013
DOI: 10.1371/journal.pone.0083346
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insight into the Genetic Context of the cadAB Genes from a 4-chloro-2-methylphenoxyacetic Acid-Degrading Sphingomonas

Abstract: The 2-methyl-4-chlorophenoxyacetic (MCPA) acid-degrader Sphingomonas sp. ERG5 has recently been isolated from MCPA-degrading bacterial communities. Using Illumina-sequencing, the 5.7 Mb genome of this isolate was sequenced in this study, revealing the 138 kbp plasmid pCADAB1 harboring the 32.5 kbp composite transposon Tn6228 which contains genes encoding proteins for the removal of 2,4-dichlorophenoxyacetic acid (2,4-D) and MCPA, as well as the regulation of this pathway. Transposon Tn6228 was confirmed by PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 53 publications
0
36
0
Order By: Relevance
“…The known genes responsible for 2,4-D degradation are the tfdABCEDF gene cluster (19) and the cadABCD gene cluster (20), and they were all present in at least one of our isolates. In brief, cadABCD encodes a protein complex that catalyzes the first step of the 2,4-D biodegradation pathway, which converts 2,4-D to 2,4-dichlorophenol (2,4-DCP), similar to tfdA; the tfdBCEDF cluster encodes enzymes for the subsequent steps.…”
Section: Figmentioning
confidence: 87%
See 1 more Smart Citation
“…The known genes responsible for 2,4-D degradation are the tfdABCEDF gene cluster (19) and the cadABCD gene cluster (20), and they were all present in at least one of our isolates. In brief, cadABCD encodes a protein complex that catalyzes the first step of the 2,4-D biodegradation pathway, which converts 2,4-D to 2,4-dichlorophenol (2,4-DCP), similar to tfdA; the tfdBCEDF cluster encodes enzymes for the subsequent steps.…”
Section: Figmentioning
confidence: 87%
“…Its genome sequence revealed cad genes showing 100% nucleotide identity with a homolog from a previously described conjugative plasmid, pCADAB1, encoded by Sphingobium sp. ERG5 (Alphaproteobacteria) (20). The cad gene cluster identified in the Novosphingobium sp.…”
Section: Figmentioning
confidence: 99%
“…Among these, strains from the genus Sphingomonas have attracted wide attention for their diverse environmental adaptations and biodegradative capabilities (9,10). Strains in this genus have been shown to degrade dioxins (11), carbazole, m-xylene, biphenyl, naphthalene (12), pentachlorophenol, and many other methyl, chloro, hydroxyl, and nitroaromatic compounds (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…PFAMs are averagely encountered 1.99 times in <2kb sequences and almost double that on larger sequences (3.80 encounters/PFAM), indicating an extremely diverse population of genes on the small <2kb sequences. It is known that transposases can create circular intermediate sequences (Sekine, Aihara and Ohtsubo, 1999; Nielsen et al , 2013), and more transposases are found in short sequences than in long ones, despite the <2kb fraction only having 1/3 of the PFAM annotated genes that the longer >2kb fraction have (63 vs 50 genes respectively, data not shown). Further confirming that the small sequences <2kb are not spontaneous single-cell anomalies, the average encounters of <2kb and >2kb sequences are similar, with an average of 1.18 and 1.28 encounters per sequence, meaning that every ca fourth and fifth sequence is encountered more than once.…”
Section: Resultsmentioning
confidence: 94%